1993
DOI: 10.1093/rheumatology/32.4.281
|View full text |Cite
|
Sign up to set email alerts
|

Osteoarthritic Human Cartilage Is More Sensitive to Transforming Growth Factor   Than Is Normal Cartilage

Abstract: Osteoarthritis is a degenerative joint disease, characterized by the destruction of the articular cartilage. One of the first changes in the osteoarthritic articular cartilage is a reduction in proteoglycan content. In this study we demonstrate that transforming growth factor beta (TGF beta), a multi-functional growth factor, stimulates the proteoglycan synthesis of explants from human articular knee cartilage dose-dependently in vitro. Osteoarthritic cartilage proved to be much more sensitive to stimulation b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 0 publications
2
38
0
Order By: Relevance
“…Several lines of evidence suggest an important role for TGF-␤ in cartilage maintenance. We and others (14,15,36) showed that TGF-␤ can increase PTG synthesis in normal and OA chondrocytes in vivo and in vitro. Furthermore, local administration of TGF-␤ can suppress IL-1-induced matrix degradation (17,37), probably via down-regulating MMPs (38, 39) and/or increasing the level of TIMPs (38,40).…”
Section: Discussionmentioning
confidence: 71%
“…Several lines of evidence suggest an important role for TGF-␤ in cartilage maintenance. We and others (14,15,36) showed that TGF-␤ can increase PTG synthesis in normal and OA chondrocytes in vivo and in vitro. Furthermore, local administration of TGF-␤ can suppress IL-1-induced matrix degradation (17,37), probably via down-regulating MMPs (38, 39) and/or increasing the level of TIMPs (38,40).…”
Section: Discussionmentioning
confidence: 71%
“…In cartilage sections from normal joints, only a few chondrocytes expressed TGF-, whereas in an inflamed arthritic joint the staining of chondrocytes for TGF-s and their receptors was intense. It is known that chondrocytes respond to TGF-by increased proteoglycan (PG) synthesis [30,31], and that normal cartilage needs to be stimulated with TGF-for a few days before PG synthesis is apparent [32]. It is tempting to speculate that the expression of TGF-s on chondrocytes in an inflamed joint acts in an autocrine manner, counteracting destruction by enhancing the synthesis of PG.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a feedback loop may exist in the early stages of OA in cartilage that favors the TGF␤1 opposing effect versus IL-1. This is reinforced by the fact that chondrocytes have been shown to be more reactive to TGF␤1 in that phase of the disease, in terms of proteoglycan synthesis, for example (47). Later on, when cartilage becomes heavily eroded (fibrillated stage), the chondrocytes acquire a different metabolic behavior and do not respond in the same way to cytokines and growth factors.…”
Section: Discussionmentioning
confidence: 99%